'Manifiesto De Solidaridad Continental' Alliances and Inequalities: Inter-American Feminist Networks 1840–1948. (2nd October 2017) - Roth, Julia
ABSTRACT: Conventional narratives of the emergence of the feminist movements in the Americas focus on the US and the Seneca Falls meeting. Most works separate feminist politics from anti-racist or class struggles, and also different feminisms from one another. By contrast, this paper focuses on the connected histories and genealogies and the simultaneous articulation of diverse feminist politics in the Americas. Focusing on feminist networks between Latin America, the Caribbean and the US, the paper zooms in on, first, the context of abolitionism, transnational, and imperial feminisms emerging between 1840 and 1880, and, second, on international feminist co-operations in the context of the International Conferences of American States 1880–1948. Shedding light on the entangled histories of strategic feminist solidarities as well as their intersectional dimensions and politics, the paper seeks to encourage a more manifold imaginary of past movements and their current successors such as the 'Ni una menos' movement 2017 Women's March.